Translation studies at the interface of disciplines - "Duarte, Jo???o Ferreira, 1947-"; "Assis Rosa, Alexandra.;Seruya, Teresa, 1950-" (Amsterdam ; Philadelphia)
"A selection of papers from a conference, held at the Faculty of Letters, University of Lisbon, Nov. 2002. Includes bibliographical references and index."
Keywords: TRANSLATING AND INTERPRETING